Suitability of haematopoietic cell donors: updated consensus recommendations from the WBMT standing committee on donor issues. Issue 8 (August 2022) - Worel, Nina; Aljurf, Mahmoud; Anthias, Chloe; Buser, Andreas S; Cody, Meghann; Fechter, Mirjam; Galeano, Sebastian; Greinix, Hildegard T; Kisch, Annika M; Koh, Mickey B C; Mengling, Thilo; Nicoloso, Grazia; et al.
Summary: The contribution of related donors to the globally rising number of allogeneic haematopoietic stem cell transplantations (HSCT) remains increasingly important, particularly because of the growing use of haploidentical HSCT. Compared with the strict recommendations on the suitability for unrelated donors, criteria for related donors allow for more discretion and vary between centres. In 2015, the donor outcome committee of the Worldwide Network for Blood and Marrow Transplantation (WBMT) proposed consensus recommendations of suitability criteria for paediatric and adult related donors. This Review provides updates and additions to these recommendations from a panel of experts with global representation, including the WBMT, the European Society for Blood and Marrow Transplantation donor outcome committee, the Center for International Blood and Marrow Transplant Research donor health and safety committee, the US National Marrow Donor Program, and the World Marrow Donor Association, after review of the current literature and guidelines. Sections on the suitability of related donors who would not qualify as unrelated donors have been updated. Sections on communicable diseases, clonal haematopoiesis of indeterminate potential, paediatric aspects including psychological issues, and reporting on serious adverse events have been added. The intention of this Review is to support decision making, with the goal of minimising the medical risk to the donor and protecting the recipient from transmissible diseases.